Pengembangan Sistem Penunjang Operasional dan Pengelolaan Sumber Daya Manusia untuk Laboratorium Komputer - Angellia Debora Suryawan; Marlene Martani; Mahenda Metta Surya (Universitas Multimedia Nusantara, 2015)
Human resources are an important asset in the entire company operations activity. A human resources management support system should be provided to improve performance in accordance with the company target. The purpose of this study is to design a model of operational and human resource management support systems that can integrate employee performance data, simplify management of employee data, and generate reports in the form of Key Performance Indicator (KPI) and Binusian Level. Methodology used in this study is using literature study, design, and test a model to make operational and human resource management information system. Index Terms - human resources, operational support system, Key Performance Indicator (KPI)